Policies to mitigate health inequity: a comparison of Israel and 24 developing countries. Issue 1 (December 2016) - Cotlear, Daniel
Abstract Efforts to mitigate health inequity are at the heart of health policy in Israel and in many developing countries seeking to advance toward universal health coverage. This commentary uses the conceptual framework and the description of health policy interventions presented in a recent IJHPR article to compare policies implemented by Israel's Ministry of Health during 2011–2014 with policies under implementation in 24 developing countries, and identifies key differences and similarities. It also identifies three areas of policy where Israel seems to have strong capacities that are in high demand in developing countries. Identifying these areas of policy could help design a menu for Israeli technical assistance in health policy.